N.M.R. Investigation of Nuclear Spin Isomerism in the Ammonium Ions - Watton, Arthur (My University, 1971)
The possibility of isomeric nuclear spin states existing among the ammonium ions at low temperatures has been investigated for some twenty ammonium salts. Measurements have been made of the proton absorption signals at 4.2°K, and the temperature dependences, where previously unavailable, of the spin-lattice relaxation time.
Some of the salts exhibit the normal rigid lattice spectra and second moments characteristic of distinguishable protons, but most exhibit some degree of line narrowing at 4.2°K. The data shows that thermally activated reorientations are effectively frozen out at this temperature and cannot be responsible for such narrowing.
It is concluded that the narrow spectra, although indicative of indistinguishability among the protons, are not attributable solely to spin isomerism, but are being modified by a further mechanism, probably tunneling of the ammonium ion through the crystal field barrier.
Keywords: N.M.R., nuclear spin, isomerism, Ammonium ions, low temperatures, absorption signals, protons